Pemanfaatan Sampah Rumah Tangga Dalam Pemberdayaan Masyarakat Kelurahan Paya Mabar Kecamatan Stabat Kabupaten Langkat - Melani, Intan Suci; Putra, Ilham Mirzaya (Jayapangus Press, 2024)
Waste management includes reducing and handling waste in a sustainable, systematic and comprehensive manner. Waste is not only a cause of environmental damage, but is also a real result of human activities. Waste management can start from the smallest scale, namely by separating household waste based on type. This study attempts to determine how the community can use household waste to generate economic value, find out what obstacles occur in the procedure for managing home garbage, and discover the village government's involvement in motivating the neighborhood to dispose of waste properly. This study combines descriptive research techniques with a qualitative methodology. This study uses data reduction, data presentation, conclusion drawing, and verification as data analysis techniques. Technical triangulation as well as source triangulation are used to verify the veracity of the data in this study. Six sources were involved in the observations and interviews that produced the data. Apart from that, data was also obtained based on the outcomes of literature studies. The analysis results show that the community is still limited in managing waste, such as burning household waste and processing it into plant fertilizer, where the use of waste does not yet bring economic value to the community. Waste management has obstacles, namely the lack of adequate facilities to manage household waste properly and correctly. In waste utilization, the government's role is still minimal or lacking in managing household waste into profitable value.